Bacopa Monnieri: A Wonder Drug Changing Fortune of People - Rai, Kriti; Gupta, Nirmala; Dharamdasani, Lakshya; Nair, Pallavi; Bodhankar, Prerna (International Journal of Applied Sciences and Biotechnology, 2017)
In recent times, the use of herbal products has increased enormously across the globe. Numerous natural products such as those isolated from plants have been evaluated as therapeutics for the treatment of variety of diseases. Bacopa monnieri also referred to as water hyssop and “Brahmi,” has been used in the Ayurvedic system of medicine since time immemorial. It belongs to the family Scrophulariaceae and is an annual creeping plant found in wet, damp, and marshy areas. Phytochemical analysis of BM extracts revealed the presence of various biochemical compounds such as alkaloids, bacosides, flavonoids, glycosides, triterpenoids and saponins etc. The major therapeutic chemical constituents of this plant identified through various researches are the triterpenoids saponins, bacosides. Bacoside A has been recognized as the chief component responsible for therapeutic effects.  BM is conventionally used for diverse ailments, but is best known as memory enhancer. A vast range of studies using methanolic and ethanolic extracts of BM have shown its effect in treatment of wide range of diseases like diabetes, depression, cancer, inflammation etc. BM appears to demonstrate low toxicity in various rat, mice models including humans however, long-term studies of toxicity in humans still need to study in great details. This review focuses on the studies that have traced both pharmacological and phytochemical properties of plant Bacopa monnieri covering wide range of its effect on anti- depression, anti-inflammatory, anti-oxidative amongst many others which can surely help in betterment of mankind.Int. J. Appl. Sci. Biotechnol. Vol 5(2): 127-132